Relationship between parenting styles, identity styles and students’ internet addiction in Kerman University of Medical Sciences - Mohammad Ghaderi Rammazi (Report of Health Care, 2015)
Introduction: Improper use of the internet and its subsequent effects has recently started to be considered as an important issue. Students are among the most vulnerable groups regarding this phenomenon. Although internet addiction can be related to different parenting styles, but the use of internet provides an opportunity to seek individual’s identity. Therefore, the present study aimed to investigate the relationship between parenting styles, identity styles and students’ internet addiction in Kerman University of Medical Sciences. Methods: In this descriptive correlational type of research, the study population included all students who were addicted to the internet at Kerman University of Medical Sciences in 2014. The research sample consisted of 375 subjects selected through multi-stage cluster sampling method. All participants completed the questionnaires on internet addiction, parenting and identity styles. Results: Findings showed that among different identity styles, there was a negative correlation between informational identity style and internet addiction. Moreover, there was a positive significant correlation between diffuse/avoidant identity style and internet addiction. Concerning different parenting styles, we could observe a positive significant correlation between permissive parenting style and internet addiction, while there was a negative significant correlation between authoritative parenting style and internet addiction. Additionally, regression analysis results illustrated that students’ internet addiction level could be predicted regarding their identity styles and their parents’ parenting styles. Conclusion: It seems that applying proper parenting styles and providing the requirements of successful identity achievement can lower the incidence of internet addiction.